Synthesis and Characterization of Briquette from Carbonized Pinus Patula Saw Dust as Alternative Energy Source - Yadeta, Gemechu; Bekalu, Yihunie; Tsegaye, Mahelet; Tantu, Tegene; Haile, Fikremariam; Genene, Dagnachew; Alemu, Tewabech (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2024)
This study aimed at the synthesis and characterization of briquette from Pinus patula saw dust using different binders. The effects of particle size and type of binder on the fuel qualities of the briquette were investigated. The bulk density of biomass causes handling, storage, and transportation problems that limit its large application. Densification of biomass into briquettes can solve these problems. The experimental results indicate that briquette produced from waste paper, fruit waste, cow dung, and starch flour binders has higher calorific value, higher fixed carbon, and lower ash content. Whereas, molasses and wood ash binders decreased the calorific value and fixed carbon and increased the ash content of the briquette. As a result, a maximum calorific value of 6596 cal/g, fixed carbon content of 62.6%, and ash content of 3.66% are obtained using waste paper.  The calorific value of 6232 cal/g, fixed carbon of 48.74%, and ash content of 3.33% was obtained using fruit waste while the calorific value of 6194 cal/g, fixed carbon content of 59.94 %, and ash content of 5.35% was observed when cow dung is used. When starch flour is used, a calorific value of 6170 cal/g, fixed carbon content of 54.63%, and ash content of 2.63 was obtained. Therefore, waste paper, fruit waste, cow dung, and starch flour are promising binders that improve the fuel qualities of biomass briquettes.